THE EFFECTS OF STRATEGIC MANAGEMENT ON PERFORMANCE OF AUCTIONEER FIRMS IN KENYA - MUSYA, JOEL TITUS; RUGAMI, MR. JAMES MAINA (European Journal of Business and Strategic Management, 2016)
Purpose: The purpose of this study was to analyze the effects of strategic management on performance of auctioneer firms in Kenya Methodology: The study used descriptive survey research design. Stratified and simple random sampling methods will be used to identify the study respondents. The target population of the study were all management employees of auctioneering forms in Kenya. This study used primary data which was collected through use of Questionnaire. Data from the questionnaires was sorted, coded and input into a software for analysis. Data from the questionnaire were analysed using statistical package for the social sciences (SPSS) to generate frequencies, descriptive statistics and inferential statistics. Results: Results indicated that strategic planning had effects on performance of the auctioneering firms. Study findings further indicated that strategic implementation affects performance of the auctioneering firm. Results further indicated that organization structure affects performance of the auctioneering firms. Results also indicated that environmental characteristics affects performance of the auctioneering firms. Unique contribution to theory, practice and policy: the sturdy recommended that organization structure should be keenly observed in the management of auctioneer firms.it also recommended that further investigation be done on the effect of proper leadership practices in income generating organizations.